VERSTER, C. Inventory of documents - VERSTER, C. (ARCA, 2018)
Publications regarding Republican ideals, Boer wars, etc.
COVERAGE: 1938-1954; 0.10 metres
Keywords: VERSTER, C.; Inventories; Republican ideals; Boer war